On Existence and uniqueness to solutions nonlocal integrodifferential equations - Mutter Ismaael, Fawzi (Journal of College of Education, 2018)
The Study aims in this paper to give and investigate the existence and uniqueness of mild solutions to nonlinear functional integrodifferential equations in Banach Spaces. the fixed point theorem, according to Sadovskii and sutible necessary conditions, are concepts consulted to obtain the results in the work